2011
DOI: 10.1016/j.jval.2010.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of a Multiattribute Utility Function for the Spanish Version of the TooL Questionnaire

Abstract: Utilities from the MAUF showed good psychometric properties, serving as a complement to generic health utilities. If misapplied, however, utilities from this instrument might favor the positive evaluation of drugs showing fewer associated side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Logically inconsistent values suggested that those participants failed to either understand or concentrate on the valuation questions. Therefore, as some of the previous health state valuation studies did [19,27], we excluded some of those participants who gave multiple logically inconsistent responses. It should be noted that many EQ-5D valuation studies did not exclude logically inconsistent values and that Lamers et al [28] found that inconsistent data did not have important effects on the modeling results when estimating the EQ-5D values.…”
Section: Discussionmentioning
confidence: 99%
“…Logically inconsistent values suggested that those participants failed to either understand or concentrate on the valuation questions. Therefore, as some of the previous health state valuation studies did [19,27], we excluded some of those participants who gave multiple logically inconsistent responses. It should be noted that many EQ-5D valuation studies did not exclude logically inconsistent values and that Lamers et al [28] found that inconsistent data did not have important effects on the modeling results when estimating the EQ-5D values.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the elicitation process, methods applied are consistent with those used to develop one of the most widespread and robust generic utility measures, the HUI [ 10 , 11 ]. As has occurred in previous publications, the additive model was rejected in this study [ 10 , 11 , 42 ] and attributes were preference complements: for instance, the perceived limitation associated with being depressed and not having bladder control is greater than the separate effect of being depressed and not having bladder control, but smaller than the sum of these two problems.…”
Section: Discussionmentioning
confidence: 95%
“…Sample size was set to a minimum of 338 responders to enable the estimation of mean values with a confidence interval of ±0.032 points, and a standard deviation of 0.3 points, assuming a normal distribution of scores with a confidence interval of 95% (t-value = 1.96) [ 41 ]. However, given the complexity of the elicitation process and previous experiences [ 42 ], it was estimated that a maximum of 30% of the respondents would not be able to successfully complete all the proposed rating exercises. Hence, a total of 440 participants were interviewed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The result is expressed as a tariff ranging from 0 to 1, considering 1 the best possible state and 0 the worst. The EuroQol-5D also includes a visual analog scale (VAS) for quality of life (37). The VAS consists of a 100 mm vertical line, like a thermometer, ranging from 0 (worst imaginable health state) to 100 (best imaginable health state).…”
Section: Measurement Of Quality Of Lifementioning
confidence: 99%